Efficacy and Safety of Plazomicin in the Treatment of Enterobacterales Infections: A Meta-analysis of Randomized Controlled Trials. (29th August 2022) - Yan, Kaicheng; Liang, Beibei; Zhang, Guanxuanzi; Wang, Jin; Zhu, Man; Cai, Yun
Abstract: Background: In the present study, we aimed to compare the efficacy and safety of plazomicin with comparators for the treatment of Enterobacterales infections. Methods: Randomized controlled trials (RCTs) assessing plazomicin for Enterobacterales infections were searched on the PubMed, Embase, and Cochrane Library databases. Meta-analyses were used to evaluate the efficacy and safety in RCTs. Results: A total of 3 RCTs consisting of 761 patients were included in the present analysis. The study population included complex urinary tract infections (cUTIs), bloodstream infections (BSIs), and hospital-acquired pneumonia (HAP). Plazomicin had a clinical remission rate in the modified intention-to-treat (MITT) population that was similar to that of comparators (odds ratio [OR], 1.02; 95% CI, 0.60–1.73; I 2  = 45%) in the pooled analysis of the 3 studies. The overall microbiologic eradication rate in the microbiological MITT (mMITT) population was similar to that of the comparators group (OR, 1.46; 95% CI, 0.72–2.95; I 2  = 0%). However, the microbiologic recurrence rate of plazomicin for Enterobacterales was lower than that in the comparators group (OR, 0.38; 95% CI, 0.17–0.86; P  = .02; I 2  = 0%). No signiﬁcant differences were found between plazomicin and comparators for the risk of any adverse events (OR, 0.78; 95% CI, 0.55–1.11; I 2  = 0%). Conclusions: Plazomicin is as good as comparators in terms of efficacy and tolerance in the treatment of Enterobacterales infections. Therefore, plazomicin is a suitable choice for antibiotic treatment in adult patients with cUTIs, BSIs, or HAP.